2023
DOI: 10.1093/heapol/czad007
|View full text |Cite
|
Sign up to set email alerts
|

What accounts for the different regional responses to COVID-19 in China? Exploring the role of institutional environment, governance capacity and legitimacy

Abstract: The COVID-19 pandemic has brought enormous challenges for public health crisis management in China. Crisis responses vary greatly among provinces. Many studies focus on the role of the central government in crisis management. However, how regional governments respond to such pandemic crises is underexplored. The existing literature lacks extensive comparative studies explaining why different regions respond differently to the crisis, and how different regional institutional environments affect crisis managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…For instance, cultural tightness–looseness also varies at the state level in the US ( 139 , 144 ). Existing studies have shown that regional crisis responses are heterogeneous ( 43 , 145 ). Considering the complexity of the internal governance system of democratic countries and the cultural differences in different regions, future research can further analyze why different regions within a democratic country such as the US respond differently to crises.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, cultural tightness–looseness also varies at the state level in the US ( 139 , 144 ). Existing studies have shown that regional crisis responses are heterogeneous ( 43 , 145 ). Considering the complexity of the internal governance system of democratic countries and the cultural differences in different regions, future research can further analyze why different regions within a democratic country such as the US respond differently to crises.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Petridou and Zahariadis ( 42 ) argued that institutional, administrative and political factors are three important contextual factors affecting crisis response. Others emphasized that institutional and cultural factors are key to shaping crisis management ( 14 , 43 ). However, these studies ignore the impact of leaders’ personal contextual factor on crisis management.…”
Section: Analytical Frameworkmentioning
confidence: 99%